Access to Post-Secondary Education: How does Québec Compare to the Rest of Canada? - Finnie, Ross; Mueller, Richard (L'Actualité économique, 2017)
This research uses the Youth in Transition Survey, Reading Cohort (“YITS-A”) to analyse access to post-secondary education (PSE) in Québec in comparison to other Canadian provinces and regions. We begin by presenting access rates by region and show that university participation rates in Québec are relatively low, while college rates are high in comparison to other provinces, although these differences are presumably due in part to the cégep system in Québec. We then undertake an econometric analysis which reveals that the effects of parental education on access to PSE are much stronger than the effects of family income, and are relatively uniform across the country. The substantially weaker family income effects (stronger for females than males) figure most importantly for the Atlantic Provinces, but much less elsewhere, including in Québec. We also find that the relationships between test scores from the Programme for International Student Assessment (PISA), which measures academic ‘‘performance’’ and ‘‘ability’’ and even more so high school grades, differ by province, and are generally strongest in Ontario and weakest in Québec, again perhaps in part due to the cégep system which represents a mediating influence between high school performance and university attendance, in particular. Males are much less likely to attend university across the country, but this gap is widest in Quebec. Our analysis of traditionally under-represented and minority groups points to students from rural Québec actually being at no disadvantage in terms of PSE participation, second-generation immigrants doing especially well in comparison to other provinces, but more recent first-generation immigrants not faring nearly so well in Québec. Finally, young Québecers who do not go on to PSE (especially the Francophone majority) are much more likely than other Canadian youths to say that they simply have no aspirations to attend PSE, and to otherwise say they face no barriers to attending PSE. Policy implications are discussed using a fiscal lens.